Regional Economic Outlook, October 2005, Sub-Saharan Africa, Supplement. (Regional Economic Outlook, 2005)
This paper presents the economic outlook for Sub-Saharan Africa for 2005. Against a background of an easing of demand for imports in advanced countries, average real GDP growth is expected to decline slightly in 2005 from its strong performance in 2004. The slowdown in 2005, however, is attributable primarily to lower growth in most of the oil-producing countries following the exceptional increases in oil production capacity established during 2003 and 2004, especially in Nigeria. Non-oil-producing countries are expecting average growth of about 4.5 percent, similar to that observed in 2004.